1993
DOI: 10.1530/acta.0.1290573
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Cu/Zn and Mn superoxide dismutase in various thyroid disorders

Abstract: The intracellular localization of Cu/Znand Mn-superoxide dismutases (SOD), which catalyze the dismutation of superoxide radicals (O2\m=-\) to O2 and H2O2, was studied in the thyroid tissue of various thyroid disorders by an immunohistochemical technique. The concentrations of both SODs in those tissues were measured also by a sandwich enzyme immunoassay technique.Copper/zinc-SOD in thyroid tissues were identified by immunocytochemical staining in most cases of papillary carcinoma and in some cases of other thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…Other authors have estimated the concentration rates of Cu/Zn in the cancerous thyroid tumor were significantly higher than in the normal and other thyroid diseases. 16,17 This study also confirmed that the cancerous thyroid tissues have higher Cu concentrations than the non-cancerous (adenoma) thyroid…”
Section: Determination Of Copper and Zinc In Human Thyroid Tissuessupporting
confidence: 73%
“…Other authors have estimated the concentration rates of Cu/Zn in the cancerous thyroid tumor were significantly higher than in the normal and other thyroid diseases. 16,17 This study also confirmed that the cancerous thyroid tissues have higher Cu concentrations than the non-cancerous (adenoma) thyroid…”
Section: Determination Of Copper and Zinc In Human Thyroid Tissuessupporting
confidence: 73%
“…In opposite to our results Reddy et al (16) have reported lower levels of Cu in the tissue of cancerous thyroid than in normal thyroid tissue and like our results (our results are refl ecting serum levels), much lower levels of Cu in the tissue of thyroid adenoma. Other authors have estimated the concentration rates of Cu/Zn in the cancerous thyroid tumour were signifi cantly higher than in the normal and other thyroid disease (12,17,18).…”
Section: Discussionmentioning
confidence: 94%
“…Growth factor levels appeared to be increased (VEGF-A, 5.6-fold; EGFL9, 8.9-fold; PDGFC and PDGFRB, 8.4-and 3.8-fold, respectively; IGF1R, 2.2-fold; and IGBP1, 30-fold) in post-Chernobyl PTC group compared to the control PTC group, thus supporting the hypothesis that aggressiveness, lymph node metastasis and venous invasion might be linked with growth factor mRNA levels. Likewise, it has been shown by many authors that increased mRNA or protein levels of oxidoreductases such as cyclooxygenase 2 (PTGS2), superoxide dismutase (SOD1) and, in some studies, thyroid peroxidase (TPO) are characteristic of thyroid malignancies (42)(43)(44)(45), which was again linked with age (46) and poorer prognosis. In our experiments, mRNA levels of TPO and SOD3 measured in post-Chernobyl PTC appeared to be increased twoand 3.4-fold over the control group, respectively, again supporting the hypothesis that tumor aggressiveness could be linked to oxidoreductase mRNA levels.…”
Section: Figmentioning
confidence: 99%